Experience of using vegetal enterosorbent in the treatment of acute intestinal infections - D. A. Lioznov; S. K. Sajfullin; I. N. Kuznetsova; S. L. Nikolaenko; A. T. Zhurkin (Журнал инфектологии)
New approaches to pathogenetic therapy of acute intestinal infections remains a priority for clinical practice. Seventy one patients 71 with acute intestinal infections were include in the study. Thirty three patients of the treatment group received Mukofalk. Patients from treatment group recorded stool normalization earlier than those in the control group (2,9±0,9 days and 4,1±1,2 days of treatment, respectively, p<0,05). Relief of abdominal pain was also observed in earlier periods: the treatment group up to 1,5±0,5 during stay in hospital, control group – 1,9±0,7 days (p <0,05). During the course of the disease (5-6 days of treatment), the median level of inerleukin-8 in patients of the treatment group was significantly lower than the control group's (8,1 (4,6; 18,1) pg/ml and 22,3 (12,35; 29,35) pg/ml, respectively, p<0,01). This data allows us to recommend the inclusion of Mukofalk in complex therapy of acute intestinal infections.